Outcomes and special techniques for treatment of penile amputation injury. (December 2019) - Djordjevic, Miroslav L.; Bizic, Marta; Stojanovic, Borko; Joksic, Ivana; Bumbasirevic, Uros V.; Ducic, Sinisa; Mugabe, Herbert; Krstic, Zoran; Bumbasirevic, Marko Z.
Abstract: Introduction: Management of severe penile trauma presents great challenges for reconstructive urologists since these injuries vary from abrasions to total emasculation. A review of our case experience with penile amputation is presented, emphasizing techniques used to salvage or reconstruct the most difficult of penile injury cases. Materials and methods: A total of 13 patients with penile amputation injury referred to us between 2007 and 2016 were analyzed. Mean age at surgery was 16 years (ranged from 4 to 29 years). Etiology of penile amputation (partial or total) combined with management and outcomes were evaluated. Management included different surgical procedures with the aim to achieve good functional and esthetical outcomes. Postoperative questionnaire was used for assessment of patient's overall satisfaction. Results: Follow-up ranged from 13 to 182 months (mean 53). Causes of penile injury were iatrogenic trauma (8), self-amputation (2), electrocution (1), intentional sexual assault (1) and mother's hair strangulation (1). Outcome criteria including aesthetic appearance, urinary function and ability to engage in satisfactory coitus, were noted in 11 cases (85%). Two cases with ensuing complications relating to the total phalloplasty required additional treatment due to urethral fistula. Conclusions: Severe penile injuries should be treated on a case by case basis utilizing the most propitious techniques. We respectfully propose that the needs of such patients are best served by referral centers with extensive experience.